(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
The article talks about the methodological foundations of the development of modern science and technology and the methods of the emergence of scientific and technical knowledge. Several aspects of natural language and technical intelligence are demonstrated.